Share the Music : Creating Musical Moods - Blackstone, Wendy (McGraw-Hill School Publishing Company, 1995)
Film composer Wendy Blackstone shows how music can define and embellish the meaning of images. After exploring the synthesizer and comparing the effects of film clips set to different scores, students discuss how music helps create moods.